The archaeology of the Jesuit missions in Ethiopia (1557-1632) - Fernández, Víctor M.; De Torres, Jorge; Martínez d'Alós-Moner, Andreu; Cañete, Carlos (Jesuit studies (Leiden, Netherlands), 2017)
One of the earliest and most ambitious projects carried out by the Society of Jesus was the mission to the Christian Kingdom of Ethiopia, which ran from 1557 to 1632. In about 1621 crucial figures in the Ethiopian Solomonid monarchy, including King Susenyos, were converted to Catholicism and up to 1632 imposing missionary churches, residences and royal structures were built. This book studies for the first time in a comprehensive form the missionary architecture built by the joint work of Jesuit padres, Ethiopian and Indian masons and royal Ethiopian patrons. The work gives ample archaeological, architectonic and historical descriptions of the ten extant sites known to the date and includes hypotheses on hitherto unexplored or lesser known structures.